Religious Analysis of Negative Brand Name Product Purchasing Decisions among State General College Students and Students at Islamic Religious Colleges in Surabaya - Dewi, Hapsari Shinta Citra Puspita; Erta, Erta; Putra, Nur Salsabila Rhesa Pandhadha (International Journal of Emerging Research and Review, 2024)
Objectives: Quite rapid developments in the culinary world have been experienced in various countries, one of which is Indonesia. The culinary world is one of the contributors to the national creative industry. The unique concept developed in the business world is one of the marketing strategies that can be carried out by business people. Determining a brand can be done as a strategy by business people so that it is easily recognized and able to attract people's interest in buying. In East Java, there are currently many restaurants with unique, interesting names that even seem to have negative connotations. The names of the restaurants above show that there are business names that use brand names with negative connotations to attract the attention of their customers. Method: The research locations are Universitas Negeri Surabaya (Unesa) and Surabaya State Islamic University (Uinsa). Respondents were 112 students consisting of 50 Unesa students and 63 Uinsa Surabaya students. A quantitative descriptive research method using closed and open questionnaire measuring instruments. Results: Based on the religious results adopted for consideration, the consistent value of purchasing decisions for negative brand name products is 123.740. Meanwhile, the regression coefficient is negative, namely -0.306, which means that every addition or increase in religiousness will reduce the decision to purchase negative brand name products. Negative brand names influence purchases made by students of Surabaya state universities and Islamic universities, which both influence the level of religiosity in purchasing decisions. Novelty: This research focuses on negative brand names. Religiosity is seen from students from religious and general higher education backgrounds. Apart from that, this research was also conducted in the most congested city in Indonesia, namely Surabaya.